Тоталітаризм в інформаційному середовищі - Нестеренко, В. В. (ХНУРЕ, 2021)
Information technologies – the supremacy of methods and methods, how to get used for picking, collecting, processing and expanding information in the interests of the country. Totalitarianism is a type of political power, the establishment of a wide ideological manipulation, terror and violence. Having summed up two terms, it is recognized as new – "information totalitarianism", that is, totalitarianism in the information middle. Over the last ten years, information technologies have developed and expanded even more rapidly. The Internet became the number one in the list of information technologies. Vlady deyakikh krains have seen digital totalitarianism on the Internet for a long time.
Keywords: філософія; тоталітаризм